Job discretion and job satisfaction in Germany - LIM, Kyungwon (KDI School, 2017)
This research aims to find the impact of the institutional differences between the regimes of East and West Germany on job satisfaction and discretion. By using the division of Germany for 45 years after the World War II as a natural experimental setting with the data from the German Socio-Economic Panel (SOEP) from 1990 to 2009, I find that the workers of East German origin (the Easterners) have a lower level of job satisfaction after 20 years of the German reunification compared to their western counterparts. In addition, when the same amount of job discretion is granted, the Easterners exhibited a higher level of job satisfaction since they might be more appreciative of job discretion that they could not experience under the communist regime. However, this phenomenon disappeared after ten years. I also investigate the impact of migration to the region of West Germany after the reunification from East Germany. I found that among Easterners, migrants had higher job satisfaction than non-migrants but migrants experienced lesser increase in job satisfaction determined by job discretion.
Thesis(Master) --KDI School:Master of Development Policy,2017